A Study on Job Anxiety, Turnover Intention and Job Satisfaction of Aviation Security Search Employees - Choi, Jeong Il; Jang, Ye Jin (International Journal of Advanced Science and Technology, 2019)
Background/Objectives: The purpose of this study is to analyze the effect of job insecurity on job turnover and job satisfaction. Research model and research hypotheses were set up, and surveys were conducted for the personnel in charge of security work at the airport.Methods/Statistical analysis: In order to analyze the effect of job security anxiety on turnover intention and job satisfaction, this study was conducted to survey employees who are in charge of security search at airport. The study period was from November 6, 2017 to November 17, 2017 for about 2 weeks. In the questionnaire, the variables were divided into three categories: "First, job anxiety, Second, turnover intention, Third, job satisfaction".Findings: Prior to this study, previous studies have examined the employment insecurity, turnover intention and job satisfaction of aviation security search workers. Research hypotheses have examined the effects of employment insecurity on job turnover and job satisfaction. Analysis results showed that employment insecurity affects turnover intention and turnover intention affects job satisfaction. However, employment anxiety did not directly affect job satisfaction, so it was explained that employment stability was not linked to job satisfaction. Therefore, it is analyzed that more attention should be paid to the turnover intention before the employment anxiety is resolved. In conclusion, in order to improve the job satisfaction of aviation security searchers, efforts should be made to reduce the factors shown in the turnover intention.Improvements/Applications: In addition, there should be a lot of interest in pay increase opportunity, promotion possibility and employment stability, which are caused by employment insecurity.Keywords: Aviation Security Search, Security Personnel, Job Insecurity, Turnover Intention, Job Satisfaction